The Relation between Diversification Strategy and Organizational Performance: A Research on Companies Registered to the Istanbul Stock Exchange Market - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
The aim of this study is to examine the relationship between applications of diversification strategies and organizational performance realized during the recent economic crisis. Rumelt classifies diversification strategies into concentric diversification, core business-based diversification, related diversification and unrelated diversification. Diversification strategy and organizational performance relationship seems to differ across the developed and developing countries under stable conditions. Studies on this relationship in developed countries carried out by the year 2000 yielded the generally accepted conclusion that the relationship between diversification strategies and organizational performance is in the form of an inverted U curve. It is observed that the researches carried out after 2000 are focused on determinants of the relationship. The result in developed countries is that the relationship between diversification strategies and organizational performance increases up to the medium value then shows a decrease in performance. However, there exist studies with the conclusion that the indicators of the relationship between diversification strategies and organizational performance of developed countries differ from the indicators of developing countries due to the effects of government and business relations, market, production, labor factors, and political economic variables. The universe of the research is determined to be a total of 318 companies listed on the Istanbul Stock Exchange o whose shares got traded in 2007. The dependent variable of the research is organizational performance and the independent variable is the measure of diversification. Rumelt's classification is utilized as a measure of diversification. Financial values of ROA and ROS are used as a measure of organizational performance. With regard to the findings of the research carried out in Turkey, the relationship between diversification strategies and organizational performance varies dependent on the developed countries. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: Diversification strategy; organizational perfomance; diversification strategy in the emerging market; Rumelt's diversification measure; RISK-RETURN PERFORMANCE; CORPORATE DIVERSIFICATION; EMERGING MARKETS; TECHNOLOGICAL DIVERSIFICATION; PRODUCT DIVERSIFICATION; BUSINESS GROUPS; FIRMS